2019
DOI: 10.1101/2019.12.19.19015446
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A public health approach to cervical cancer screening in Africa through community-based self-administered HPV testing and mobile treatment provision

Abstract: Background: Sub-Saharan Africa bears the world's highest incidence of cervical cancer. To address the lack of widespread screening and treatment that contributes to this burden, the World Health Organization (WHO) recommends that low-resource countries adopt simplified protocols for screening directly coupled with treatment. The WHO recommendations present an opportunity -- akin to what has been done for HIV care in Africa -- for a true public health approach to cervical cancer control in resource-poor setti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…Strategies to implement HPV testing as primary screening include community‐based interventions to increase coverage of screening, especially in rural areas where access to health facilities may be limited. Community health campaigns and home visits by community health workers in particular have been shown to increase screening uptake, especially when women are given the option to self‐collect samples for HPV testing 18‐24 . A study in Uganda found over 99% compliance among women who were offered HPV tests by self‐collection, whereas VIA at a health clinic reached only approximately 48% compliance, given that self‐collection allowed women to provide samples immediately upon recruitment by health workers at home or work visits 23 .…”
Section: Hpv Dna Testing As a Cervical Cancer Screening Method: Next ...mentioning
confidence: 99%
See 3 more Smart Citations
“…Strategies to implement HPV testing as primary screening include community‐based interventions to increase coverage of screening, especially in rural areas where access to health facilities may be limited. Community health campaigns and home visits by community health workers in particular have been shown to increase screening uptake, especially when women are given the option to self‐collect samples for HPV testing 18‐24 . A study in Uganda found over 99% compliance among women who were offered HPV tests by self‐collection, whereas VIA at a health clinic reached only approximately 48% compliance, given that self‐collection allowed women to provide samples immediately upon recruitment by health workers at home or work visits 23 .…”
Section: Hpv Dna Testing As a Cervical Cancer Screening Method: Next ...mentioning
confidence: 99%
“…Offering self‐sampling options for HPV testing can be advantageous, because it allows task shifting to the women themselves, especially in light of frequent provider shortages in low‐resource settings 27 . The quality of self‐collected samples is comparable to clinician‐collected samples, 28‐33 and women also consider self‐collection to be acceptable, adequately private, and preferable over clinician‐collected sampling 20,30,34,35 . However, despite the general acceptance of self‐collection among women, lack of confidence in and awareness of HPV testing and self‐collection have also been reported in some contexts as barriers to screening uptake 16,27,36‐38 .…”
Section: Hpv Dna Testing As a Cervical Cancer Screening Method: Next ...mentioning
confidence: 99%
See 2 more Smart Citations